2012
DOI: 10.2519/jospt.2012.3987
|View full text |Cite
|
Sign up to set email alerts
|

Trunk, Pelvis, Hip, and Knee Kinematics, Hip Strength, and Gluteal Muscle Activation During a Single-Leg Squat in Males and Females With and Without Patellofemoral Pain Syndrome

Abstract: Study Design Controlled laboratory study using a cross-sectional design. Objectives To determine whether there are any differences between the sexes in trunk, pelvis, hip, and knee kinematics, hip strength, and gluteal muscle activation during the performance of a single-leg squat in individuals with patellofemoral pain syndrome (PFPS) and control participants. Background Though there is a greater incidence of PFPS in females, PFPS is also quite common in males. Trunk kinematics may affect hip and knee functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
263
6
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(323 citation statements)
references
References 52 publications
(109 reference statements)
16
263
6
18
Order By: Relevance
“…Additionally, it has been shown that there are gender specific differences in hip abduction strength (Brent et al,2013;Ramskov et al, 2014), gluteal activation (Nakagawa et al, 2012) and trunk and lower limb kinematics (Nakagawa et al, 2012, Willy et al, 2012a in both the normal and PFP population. There have been shown to be differences in hip strength deficits in males and females in PFP (Rathleff et al, 2014) suggesting that rehabilitation and future research trials should be gender specific.…”
Section: Hip Strengthening Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has been shown that there are gender specific differences in hip abduction strength (Brent et al,2013;Ramskov et al, 2014), gluteal activation (Nakagawa et al, 2012) and trunk and lower limb kinematics (Nakagawa et al, 2012, Willy et al, 2012a in both the normal and PFP population. There have been shown to be differences in hip strength deficits in males and females in PFP (Rathleff et al, 2014) suggesting that rehabilitation and future research trials should be gender specific.…”
Section: Hip Strengthening Exercisementioning
confidence: 99%
“…However, evidence demonstrating that reduced muscle strength is accompanied by altered hip kinematics in PFP is conflicting, with some studies showing an association between a reduction in muscle strength with altered kinematics (Boling and Padua, 2013;Souza and Powers, 2009;Nakagawa et al, 2012) and others that there is not (Willson et al, 2008). There is delayed onset and shorter activation of gluteus medius in adults with PFP (Barton et al, 2013) and some evidence to show that altered gluteal muscle activation patterns accompanies altered hip kinematics in PFP (Souza and Powers 2009;Nakagawa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was a trial to investigate not only the available evidence for physical interventions for Patellofemoral pain syndrome , and also to see the effective approach. (13,14) Fukuda et al ,2010 conducted a randomized controlled trial for the treatment of PFPS, in this study hip strengthening exercises and knee strengthening exercises were done. Combined effect of both exercises was found to be effective during a treatment session of 4 weeks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Outro estudo prospectivo (113) Durante atividades dinâmicas, movimentos anormais ou instabilidade do tronco podem refletir em estratégias compensatórias dos membros inferiores (13) . A fraqueza dos músculos abdutores pode levar a um deslocamento ipsilateral do tronco em atividades unipodais, esta estratégia compensatória transfere o centro de massa corporal para o centro da articulação do quadril, diminuindo a sobrecarga sobre os abdutores do quadril (13,114) .…”
Section: Força Do Quadril E Troncounclassified